Competitive athletic participation, thigh muscle strength, and bone density in elite senior athletes and controls - McCrory, J. L.; Salacinski, A. J.; Hunt Sellhorst, S. E.; Greenspan, S. L. (The Journal of Strength and Conditioning Research, 2013)
The relationship between participation in highly competitive exercise, thigh muscle strength, and regional and total body bone mineral density (BMD) in elite senior athletes and healthy elderly controls was investigated. One hundred and four elite senior athletes (age: 72.6 ± 6.4 years, height: 168.7 ± 8.6 cm, mass: 72.6 ± 13.5 kg, 57 male:47 female) and 79 healthy controls (age: 75.4 ± 5.6 years, height: 170.8 ± 25.5 cm, mass: 79.5 ± 11.7 kg, 46 male:33 female) participated in this cross-sectional study. Vitamin D and calcium intake were assessed via a recall survey. Isometric knee extension and flexion peak torque were measured via a custom strength measurement device. Total body and regional BMD of the hip, radius, and spine were assessed with a dual-energy x-ray absorptiometer. For each BMD site assessed, multivariate linear regression analysis was performed in 4 steps (a = 0.10) to examine the contribution of (a) age, sex, bodyweight, and calcium and vitamin D intake; (b) group (elite senior athlete, control); (c) knee extension peak torque; and (d) knee flexion peak torque on BMD. Sex, age, bodyweight, and calcium and vitamin D intake explained a significant amount of variance in BMD in each site. Group was not significant. Knee extension peak torque explained an additional 3.8% of the variance in hip BMD (p = 0.06). Knee flexion peak torque was not correlated to BMD at any of the sites assessed. In conclusion, participation in highly competitive athletics was not related to total body or regional BMD. Age, sex, bodyweight, and vitamin D and calcium intake were significantly related to BMD at all the sites assessed. Quadriceps strength contributed slightly to hip BMD. Our results imply that participation in highly competitive senior athletics does not have a protective effect on BMD, perhaps because of a lower bodyweight or other confounding factors.